Increased radiosensitivity and impaired DNA repair in patients with STAT3-LOF and ZNF341 deficiency, potentially contributing to malignant transformations - AYDINER, ELİF; ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA (My University, 2022)
STAT3 plays an important role in various complex and sometimes contradictory pathways such as proliferation, differentiation, migration, inflammation, and apoptosis. The transcriptional activity of the STAT3 gene is controlled by a transcription factor called ZNF341. There is insufficient data on radiation sensitivity and post-radiation DNA repair in STAT3- loss-of-function (LOF) patients. We aimed to investigate the radiosensitivity in patients with STAT3-LOF and ZNF341 deficiency. Twelve patients with STAT3-LOF and four ZNF341-deficiency patients were recruited from three clinical immunology centers in Turkey and evaluated for radiosensitivity by the Comet assay, comparing to 14 age- and sex-matched healthy controls. The tail length (TL) (mu m), percentage of DNA in the tail (TDNA%), and olive tail moment (OTM) (arbitrary units) were evaluated at the same time for baseline (spontaneous), initial (immediately after 2 Gy irradiation), and recovery (2 h after irradiation) periods by using a computerized image-analysis system, estimating DNA damage. Except for a patient with ZNF341 deficiency who developed nasal cell primitive neuroendocrine tumor and papillary thyroid cancer during the follow-up, there was no cancer in both groups. During the recovery period of irradiation, TL, TDNA%, and OTM values of healthy controls decreased rapidly toward the baseline, while these values of patients with STAT3-LOF and ZNF341 deficiency continued to increase, implying impaired DNA repair mechanisms. Increased radiosensitivity and impaired DNA repair were demonstrated in patients diagnosed with STAT3-LOF and ZNF341 deficiency, potentially explaining the susceptibility to malignant transformation.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); IMMUNOLOGY; Life Sciences (LIFE); Genel İmmünoloji ve Mikrobiyoloji; Immunology; General Immunology and Microbiology; STAT3-LOF; ZNF-341 deficiency; radiosensitivity; DNA repair; Comet assay; HYPER-IGE SYNDROME; ENHANCES RADIOSENSITIVITY; CANCER-PATIENTS; IN-VITRO; MUTATIONS; DAMAGE; CELLS; STAT3-LOF; ZNF-341 deficiency; radiosensitivity; DNA repair; Comet assay